Request as a Speech Act: A Study of the Features of the Spoken Nigeria English - Utin, Iniobong Dominic (NIU Journal of Social Sciences, 2024)
This study examines Request expressions as speech acts in Spoken Nigerian English. Subjects for this study were drawn from the University of Port Harcourt. Data for this study were collected from two different speech interactions, namely: face-to-face conversations (FTFC), telephone conversations (TC). The researcher made use of a mini-tape recorder and note-taking method for data collection. Here, Corpus of conversations were selected using purposive sampling method and surreptitiously recorded at strategic points. This enabled the researcher to collect the Corpus in its original form. The Corpus for this study was collected at different points where the students meet: lecture halls, hostels, canteens, relaxation centres among others. From the data collected through a purposive sampling method, request expressions were isolated and used for the analysis.  The framework for the analysis of this study is provided by the speech Act theory. Frequency of the distribution between the male and female subjects, were calculated using the mean statistical method and subsequently represented in bar charts. This study found out that beyond the main function of request, it also performs an array of other functions. Data have also revealed that the multilingual situation in Nigeria has affected the choices of language use, resulting in features such as code-mixing, slangs, Nigerian English-based pidgin, among others. This study has specifically shown that apart from the usual function of request, it also performs an array of other functions. Therefore, this study concludes that with regard to the selected speech act, the co-existence of English with other indigenous languages has given rise to linguistic patterns and forms, identifying Nigerian English as a distinct variety of the world Englishes. Keywords: Request Expressions, Speech Acts, Nigerian English, Gender Difference.